Genetic dissection of nutrient element enrichment in Saccharum officinarum L. for deciphering the food health - Fan, Lina; Chachar, Zaid; Chen, Ming; Li, Yucong; Chen, Jiarui; He, Huiyi; Wen, Jiakun; Gul, Saira; Lai, Ruiqiang; Qi, Yongwen (Frontiers in Plant Science, 2025)
IntroductionSugarcane is a critical global crop, primarily used for sugar production, with applications spanning the food, industrial, and pharmaceutical sectors. Improving nutrient efficiency in sugarcane varieties is essential to enhance yield, ensure sugar security, and improve nutritional value.MethodsThis study analyzed 109 sugarcane stem segment samples to assess major (magnesium, calcium, phosphorus) and trace (manganese, iron, copper) nutrient content, along with SNP genotyping data. Two multi-model Genome-Wide Association Study (GWAS) approaches—MLM_Q+Kinship and MLM_PCA+Kinship—were employed to identify SNPs associated with nutritional traits.ResultsUnder a P-value threshold of <10⁻⁴, the MLM_Q+Kinship approach identified SNPs linked to several traits, including total sugar (4), nitrogen (7), phosphorus (179), potassium (4), sulfur (41), magnesium (26), calcium (20), and silicon (66). Similar results were obtained with MLM_PCA+Kinship. A stricter threshold (P < 1.53×10⁻⁶) yielded 59 reliable "Peak" SNP loci, which explained over 15% of phenotypic variance. Notably, SNPs 3B_33126337 and 5C_64683842 were strongly associated with magnesium, calcium, and iron utilization. Genotypic analysis revealed superior nutrient accumulation in genotypes TT (3B_33126337) and AA/AG (2D_29369331, 3B_14919731). Bioinformatics analysis identified 12 candidate genes involved in magnesium, calcium, and manganese metabolism, linked to pyruvate metabolism, purine metabolism, and glycolysis/gluconeogenesis pathways. RT-qPCR analysis confirmed significant expression differences in three genes (Sspon.003B0015150, Sspon.002D0013560, and Sspon.003B0007030) between genotypes, suggesting their potential as key targets.ConclusionThese findings provide valuable genetic markers and candidate genes for the development of nutrient-efficient, high-yield sugarcane varieties, contributing to advancements in both agriculture and nutrition.